Analysis of 11C-methionine Uptake in Low-Grade Gliomas and Correlation with Proliferative Activity - Kato, T.; Shinoda, J.; Oka, N.; Miwa, K.; Nakayama, N.; Yano, H.; Maruyama, T.; Muragaki, Y.; Iwama, T. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: The relationship of 11C-methionine (MET) uptake and tumor activity in low-grade gliomas (those meeting the criteria for World Health Organization [WHO] grade II gliomas) remains uncertain. The aim of this study was to compare MET uptake in low-grade gliomas and to analyze whether MET positron-emission tomography (PET) can estimate tumor viability and provide evidence of malignant transformation.MATERIALS AND METHODS: We studied glioma metabolic activity in 49 consecutive patients with newly diagnosed grade II gliomas by using MET PET before surgical resection. On MET PET, we measured tumor/normal brain uptake ratio (T/N ratio) in 21 diffuse astrocytomas (DAs), 12 oligodendrogliomas (ODs), and 16 oligoastrocytomas (OAs). We compared MET T/N ratio among these 3 tumors and investigated possible correlation with proliferative activity, as measured by Mib-1 labeling index (LI).RESULTS: MET T/N ratios of DA, OD, and OA were 2.11 ± 0.87, 3.75 ± 1.43, and 2.76 ± 1.27, respectively. The MET T/N ratio of OD was significantly higher than that of DA (P < .005). In comparison of MET T/N ratios with the Mib-1 LI, a significant correlation was shown in DA (r = 0.63; P < .005) but not in OD and OA.CONCLUSION: MET uptake in DAs may be closely associated with tumor viability, which depends on increased amino acid transport by an activated carrier-mediated system. DAs with lower MET uptake were considered more quiescent lesions, whereas DA with higher MET uptake may act more aggressively.